Changes in Faculty Members' Instructional Beliefs while Implementing Model‐Eliciting Activities. Issue 3 (14th July 2015) - Moore, Tamara J.; Guzey, S. Selcen; Roehrig, Gillian H.; Stohlmann, Micah; Park, Mi Sun; Kim, Young Rae; Callender, Hannah L.; Teo, Hon Jie
Abstract Background Engineering Faculty members should adopt effective pedagogical approaches in order to maximize student learning. The beliefs of faculty members about instructional practice are an important construct in determining what and how they teach. Purpose This study investigates the effect of faculty members' involvement in model‐eliciting activities on their beliefs about classroom instruction. This study is guided by the following research question: How do faculty members' beliefs about teaching, learning, and assessment change through the use of model‐eliciting activities (MEAs)? Design/Method Using a multicase study design, four engineering faculty members from across the United States were studied while they developed, implemented, and assessed MEAs. Data were collected from sources including semistructured interviews about teaching beliefs and practices, a demographics and academic background survey, and biweekly surveys on MEA implementation and beliefs. Yearly interviews were coded using a rubric that classifies beliefs on a scale from instructor‐centered to student‐centered. Results Over the course of the three‐year study, the beliefs of all four faculty members shifted towards a more student‐centered view of teaching. The faculty members indicated that they were able to emphasize teamwork, real‐world practice, problem‐solving skills, timely feedback, constructed knowledge, communication, active learning, formative assessment, and the discipline of engineering through the use of MEAs. Conclusions This study provides evidence that developing and implementing MEAs can help both experienced and beginning faculty members change their beliefs toward a student‐centered view of instruction.